2016
DOI: 10.1016/j.rser.2016.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the applicability of passive cooling and heating techniques through climate factors: An overview

Abstract: A review on climate parameters affecting applicability of passive and low energy heating and cooling techniques is presented. The study has been developed from existing research work results, and aims to serve as a first-stage assessment tool of the viability of these solutions at a particular location, depending on outdoor conditions to be faced. This contribution starts with a justification of comprehensive climate analysis as the first step to evaluate whether a specific passive or low energy solution would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 111 publications
(156 reference statements)
0
23
0
1
Order By: Relevance
“…Figure 2b shows the daily maximum, minimum and average dry bulb temperatures (DBT) for a typical day of each month. It clearly shows that this climate is characterized by high DBT oscillations during typical summer days, which highlights a high potential of free-cooling for cooling period [28]. LUCIA is recognized as one of the leading and emblematic nZEB buildings in the whole World, with the one of the highest LEED certification possible, with 98 points.…”
Section: Description Of the Case Study Nzeb Building Nearly Zero Co 2mentioning
confidence: 94%
“…Figure 2b shows the daily maximum, minimum and average dry bulb temperatures (DBT) for a typical day of each month. It clearly shows that this climate is characterized by high DBT oscillations during typical summer days, which highlights a high potential of free-cooling for cooling period [28]. LUCIA is recognized as one of the leading and emblematic nZEB buildings in the whole World, with the one of the highest LEED certification possible, with 98 points.…”
Section: Description Of the Case Study Nzeb Building Nearly Zero Co 2mentioning
confidence: 94%
“…The study concluded that the efficiency of the passive strategies conditioned to both the harshness of a given climate and design of different building parameters. Tejero-González et al [5] reviewed many passive design techniques and parameters affecting applicability of such techniques. The study investigated how the climatic parameters are needed to be studied thoroughly to design and select passive cooling/heating techniques.…”
Section: Passive Cooling Systemsmentioning
confidence: 99%
“…Despite being considered as a "temperate" climate at a World scale, outdoor temperatures during winter are low enough to make heat recovery quite interesting. During summer days, large variations of temperature occur, which favors free-cooling [26]. According to the latest Köppen-Geiger classification, the typical climate of the location is Csb, hence a temperate climate with dry, warm summers [25].…”
Section: Case Studymentioning
confidence: 99%
“…Despite being considered as a "temperate" climate at a World scale, outdoor temperatures during winter are low enough to make heat recovery quite interesting. During summer days, large variations of temperature occur, which favors free-cooling [26]. The building under study is considered one of the leading nZEBs in the world, qualified with the second highest Leadership in Energy and Environmental Design LEED score in the world [27], among other certifications [6,28].…”
Section: Case Studymentioning
confidence: 99%